ANALYSIS FORMULATION STRATEGY OF PT.LUKINDARI PERMATA (ICE CREAM WALL'S DISTRIBUTOR AT SIDOARJO CITY) - Pradana, Mochamad Yusron (Jurnal Ilmiah Mahasiswa FEB, 2017)
Changes in the environment and competition is a critical factor in strategic planning that can determine opportunities or threats to the company. This study aims to analyze the influence of the environment, both internal and external environment in the company Ice cream PT.Lukindari Permata, so it can be determined appropriate strategies with companies in the face of competition.This type of research is descriptive, the research that attempts to tell the existing solution by presenting data, analyzing data, and interpreting it. The data examined covering the internal and external aspects of the company, so from there will be found opportunities, threats, strengths and weaknesses of the company in the face of increasingly tight competitors. While the analysis tools used are IFE Matrix, EFE Matrix, IE Matrix, SWOT Matrix, and QSPM Matrix.The results of this study indicate that based on analysis of internal and external environment that affect the ice cream PT.Lukindari Permata, the appropriate strategy is a combination of market penetration strategy and product development strategy. Where the market penetration strategy will increase market share of a product by increasing sales force, increasing sales promotion and other promotional efforts.Keywords: external environment, internal environment, SWOT, and strategy